2020
DOI: 10.1111/1744-7917.12821
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal‐B regulates structure and development of the Harmonia axyridis cremaster

Abstract: The ladybird Harmonia axyridis is an insect that exhibits pupal attachment to plants, which facilitates development and environmental adaptation. The cremaster is highly specialized for this behavior. However, the underlying molecular regulation of the cremaster remains unclear; therefore, we performed experiments to investigate the transcriptional regulation of cremaster development. First, we examined the morphological structure of the cremaster to reveal its function in pupal attachment of H. axyridis. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…93,[95][96][97] Furthermore, inhibition of Abd-B expression has been reported to have drastic morphological effects, including transforming ovipositors into legs or antennae 65,[72][73][74] and the development of prolegs on segments A7-A9 to develop, indicating that Abd-B is critical for restraining appendage development in the posterior abdominal segments. 75,[98][99][100] Our data showed that RNAi-induced knockdown of SfAbd-B in females caused a genitalia-to-leg transformation in addition to replacing the first and second valvulae on the ovipositors with one pair of protruding appendages. SfAbd-B RNAi also resulted in stunted posterior abdominal segments and failed wing expansion, suggesting SfAbd-B is essential for their normal development in WBPH.…”
Section: Discussionmentioning
confidence: 70%
“…93,[95][96][97] Furthermore, inhibition of Abd-B expression has been reported to have drastic morphological effects, including transforming ovipositors into legs or antennae 65,[72][73][74] and the development of prolegs on segments A7-A9 to develop, indicating that Abd-B is critical for restraining appendage development in the posterior abdominal segments. 75,[98][99][100] Our data showed that RNAi-induced knockdown of SfAbd-B in females caused a genitalia-to-leg transformation in addition to replacing the first and second valvulae on the ovipositors with one pair of protruding appendages. SfAbd-B RNAi also resulted in stunted posterior abdominal segments and failed wing expansion, suggesting SfAbd-B is essential for their normal development in WBPH.…”
Section: Discussionmentioning
confidence: 70%
“…Abd-B plays a key role in regulating cremaster (a specialized tail organ) development during the pre-pupal stage of the ladybird beetle Harmonia axyridis(Zhang et al, 2020). In our present study, the annulatedF I G U R E 6 Different levels of larval phenotypic changes resulted from Abd-Bs RNAi.…”
mentioning
confidence: 54%
“…A similar phenotype is visible in Tribolium larvae and Oncopeltus hatchlings, wherein reduction of Abd‐B activity transforms abdominal segments to adopt a more anterior identity and leads to ectopic terminal structures (Angelini & Kaufman, 2005; Beeman et al, 1989; Wool & Medlinger, 1973). A recent study revealed that Abd‐B plays a key role in regulating cremaster (a specialized tail organ) development during the pre‐pupal stage of the ladybird beetle Harmonia axyridis (Zhang et al, 2020). In our present study, the annulated processes on A8 are abnormally‐shaped after ds Abd‐B injection, like those normally seen between the more anterior segments, suggesting a transformation to a more anterior abdominal identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antp was shown to play an important role in determining normal thoracic segments during body development of D. melanogaster and B. mori (Rosenfield & Ziff, 2006;Chen et al, 2013). Abd-B was involved in developmental regulation of testis cell identity, body pigmentation, the central nervous system and cremaster in insects (Zhang et al, 2017;Jin et al, 2019;Ghosh et al, 2019;Zhang et al, 2020). Abd-B also suppressed proleg development in posterior abdominal segments in B. mori (Tomita & Kikuchi, 2009).…”
Section: Introductionmentioning
confidence: 99%